Real-time high resolution laser speckle imaging of cerebral vascular changes in a rodent photothrombosis model - Liu, Qi (Optical Society of America, 2014)
The study of hemodynamic and vascular changes following ischemic stroke is of great importance in the understanding of physiological and pathological processes during the thrombus formation. The photothrombosis model is preferred by researchers in stroke study for its minimal invasiveness, controllable infarct volume and lesion location. Nevertheless, there is a lack in high spatiotemporal resolution techniques for real time monitoring of cerebral blood flow (CBF) changes in 2D-profile. In this study, we implemented a microscopic laser speckle imaging (LSI) system to detect CBF and other vascular changes in the rodent model of photothrombotic stroke. Using a high resolution and high speed CCD (640 × 480 pixels, 60 fps), online image registration technique, and automatic parabolic curve fitting, we obtained real time CBF and blood velocity profile (BVP) changes in cortical vessels. Real time CBF and BVP monitoring has been shown to reveal details of vascular disturbances and the stages of blood coagulation in photothrombotic stroke. Moreover, LSI also provides information on additional parameters including vessel morphologic size, blood flow centerline velocity and CBF spatiotemporal fluctuations, which are very important for understanding the physiology and neurovascular pathology in the photothrombosis model.